2015
DOI: 10.2220/biomedres.36.55
|View full text |Cite
|
Sign up to set email alerts
|

<b>Enhancing osteoblast-affinity of titanium scaffolds for bone engineering by use of ultraviolet light tr</b><b>eatment </b>

Abstract: Ultraviolet (UV) treatment immediately prior to use is attracting attention as an effective surface conditioning method for titanium to improve osteoblast-affinity. The affinity of titanium to osteoblasts in two-dimensional plate culture has been well studied, but that in three-dimensional cultures remains unclear. Here, we examined the effect of UV treatment on titanium scaffolds, comprising micro-thin titanium fibers, used in bone engineering. Titanium scaffolds, with and without UV treatment, were seeded wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…In addition, researchers have shown that the titanium implant surface is easily contaminated by hydrocarbons when stored under common conditions protected from light, which can lead to biological aging. 8 10 Our test results also confirmed that the SLA group carried the most negative charges. We used calcium ions carrying a bivalent positive charge as bridging ions.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, researchers have shown that the titanium implant surface is easily contaminated by hydrocarbons when stored under common conditions protected from light, which can lead to biological aging. 8 10 Our test results also confirmed that the SLA group carried the most negative charges. We used calcium ions carrying a bivalent positive charge as bridging ions.…”
Section: Discussionsupporting
confidence: 77%
“…This demonstrated that the carbon absorbed by the titanium surface is crucial for determining the initial affinity of the osteoblasts, and therefore, the importance of a low C/Ti ratio to increase osteoblastic activity on the titanium surface and thus obtain a higher integration [33]. Other authors, through their research, have obtained similar results [36,37,38,39].…”
Section: Discussionmentioning
confidence: 82%
“…However, when the initial healing response indicators such as fibrinogen adsorption and platelet adhesion/spreading were evaluated, there was no significant difference between 1 min and 10 min of UV irradiation; thus, it was concluded that further study was needed. Most other studies have reported that longer irradiation times result in a greater hydrophilic effect by photofunctionalization [ 15 , 23 , 24 , 25 ]. However, for clinical use, it is not appropriate to subject the patient to long treatment times, and hence we set a time of 1 min for this study.…”
Section: Discussionmentioning
confidence: 99%